Peran Bank Sentral Dalam Pengendalian Inflasi Dan Stabilitas Sistem Keuangan - Rini Puji Astuti; Anugrah Arif Ivandi; Nita Aprilia (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This research aims to analyze the role of the central bank in controlling inflation and maintaining the stability of the financial system in Indonesia. Controlled inflation and a stable financial system are two crucial aspects that support sustainable economic growth. As the monetary authority, the central bank is mandated to maintain price stability and financial system stability through monetary and macroprudential policies. The research employs a literature review method with a descriptive qualitative approach. Data were collected through document analysis, central bank annual reports, and related literature. The analysis was conducted by understanding and observing the policies implemented by the central bank in relation to macroeconomic theories and principles of financial system stability. The findings indicate that Bank Indonesia has successfully controlled inflation through the determination of benchmark interest rates and open market operations. Additionally, the implementation of macroprudential policies, such as supervision of capital adequacy ratios and bank liquidity, has strengthened the stability of the financial system